Evaluation of proprioception in denervated and healthy wrist joints. (May 2020) - Rein, Susanne; Winter, Jochen; Kremer, Thomas; Siemers, Frank; Range, Ursula; Euchner, Nane
We recruited 25 patients after complete wrist denervation and 60 healthy adults to investigate conscious and unconscious proprioception of the wrist. Ipsi- and contralateral joint-position sense, force sense, and wrist reflexes were measured. The latter were triggered by a trapdoor, recording electromyographic signals from the extensor carpi radialis brevis, extensor carpi ulnaris, flexor carpi radialis, and flexor carpi ulnaris muscles. No significant differences were found for joint position sense, force sense, and wrist reflexes between both groups, except for reflex time of the flexor carpi ulnaris after denervation of the left wrist as compared with the left flexor carpi ulnaris in controls or in right operated wrists. At a mean follow-up of 32 months (range 8 to 133), we found no proprioceptive deficit of the conscious proprioceptive qualities of joint position sense, force sense, and the unconscious proprioceptive neuromuscular control of wrist reflex time for most muscles after complete wrist denervation. We conclude from this study that complete wrist denervation does not affect the proprioceptive senses of joint position, force sense, and reflex time of the wrist.